Thermal tolerances of two stream invertebrates exposed to diumally varying temperature - Timothy J. Cox; J. Christopher Rutherford (New Zealand Journal of Marine and Freshwater Research, 2000)
For two key New Zealand freshwater invertebrates (the mayfly Deleatidium autumnale and the snail Potamopyrgus antipodarum ) the upper thermal tolerances were measured in the laboratory under both constant and diumally varying temperatures. At constant temperature 50% mortality in 96 h ( const LT 50 ) occurred at 24.2 ± 0.9°C for mayflies and 31.0 ± 0.6°C for snails: values similar to previously published estimates (Quinn et al. 1994). For diurnally varying temperatures (daily amplitude 10°C) 50% mortality occurred when the daily mean temperature was 21.9 ± 0.7°C (mayflies) and 28.6 ± 0.4°C (snails) which is c. 10% (2.5 ± 1.3°C) lower than the const LT 50 . Conversely, 50% mortality occurred when the daily maximum temperature was 26.9 ± 0.7°C (mayflies) and 33.6 ± 0.4°C (snails) which is c. 10% (2.5 ± 1.3°C) higher than the const LT 50 . Many published temperature limits for stream organisms are derived from constant temperature experiments. Our results indicate that such limits should be applied to a temperature midway between the daily average and the daily maximum of a diurnal profile.